Treatment with captopril abrogates the altered expression of alpha1 macroglobulin and alpha1 antiproteinase in sera of spontaneously hypertensive rats - Aminudin, Norhaniza; Abdullah, N. A.; Misbah, H.; Karsani, S. A.; Husain, R.; Hoe, S. Z.; Hashim, Onn Haji (BMC, 2012)
BACKGROUND: Proteins that are associated with hypertension may be identified by comparing the 2-dimensional gel electrophoresis (2-DE) profiles of the sera of spontaneously hypertensive rats (SHR) with those generated from normotensive Spraque-Dawley rats (SDR). RESULTS: Five proteins of high abundance were found to be significantly altered when the 2-DE serum profiles of the SHR were compared to those that were similarly generated from the SDR. Analysis by mass spectrometry and database search identified the proteins as retinol binding protein 4, complement C3, albumin (19.9 kDa fragment), alpha1 macroglobulin and alpha1 antiproteinase, which are all known to be associated with hypertension. The altered expression of the two latter proteins was found to be abrogated when similar analysis was performed on sera of the SHR that were treated with captopril. CONCLUSION: Our data suggests that serum alpha1 macroglobulin and alpha1 antiproteinase are potentially useful complementary biomolecular indicators for monitoring of hypertension.